KETERSEDIAAN SISTEM PROTEKSI AKTIF DAN SARANA PENYELAMATAN UNTUK MENGHADAPI BENCANA KEBAKARAN DI KAMPUS AIR TAWAR UNIVERSITAS NEGERI PADANG - Hardiyanti Rizki Saputri; Yurni Suasti; Widya prarikeslan (JURNAL BUANA, 2019)
This study aims to describe the availability of an active protection system and means of rescue and active protection system conditions in the Padang State University building Freshwater Campus. This type of research is descriptive quantitative with a population of 70 buildings at the UNP. Samples were taken by Purposive Sampling to 41 buildings with consideration of buildings that have a high risk of fire, namely laboratories, administrative buildings and lecture buildings. This study found (1) the availability of an active protection system at Padang State University is not yet complete, from 41 buildings there is only 1 building that has a total of 5 types of active protection systems. Then the availability of rescue facilities in the Padang State University building is also incomplete, from 41 buildings, there are only 5 buildings which have a total of 6 types of rescue facilities. (2) The condition of the active protection system in the Universiras Negeri Padang building is based on the level of assessment of the overall condition of 41 buildings, where all have values in the range <60 and are included in the less category.